Renewed for murder - Gilbert, Victoria (Gilbert, Victoria. Blue Ridge library mystery., 2021)
Amy Webber and her new husband Richard Muir are settling into married life - and a new project. Richard is choreographing a suite based on folk music and tales, while Amy scours the library's resources for background information on the dance's source material. But the mellifluous music comes to a halt when an unknown woman's body turns up in Zelda Shoemaker's backyard gazebo. Chief Deputy Brad Tucker puts Zelda at the top of his suspect list, thanks to a blackmail letter he finds in the dead woman's pocket but Zelda's best friend, Amy's aunt Lydia Talbot, begs Amy to use her research to clear Zelda's name. But the task is confounded by Zelda's refusal to reveal why the victim might have blackmailed her.